Differences in the match performance of Asian women`s football teams - Wang, S. H.; Qin, Y. (Journal of Physical Education and Sport, 2020)
The aim of this study was to identify the technical and tactical differences between Chinese, Japanese, South Korean, and Chinese Taipei women football teams according to their overall competitive ability, playing positions, and the competitive ability of key players. The analysis was based on 50 matches in the World Women's Cup, Algarve Cup, and East Asian Cup. The variables studied included: percentage of ball possession, percentage of ball possession in the final third, passes, pass accuracy, through passes, proportion of through passes, through pass accuracy, entries to the final third, 1vs1 success rate, shots, shots on target, goals, and ground and aerial duels and their success rate. Discriminant and ANOVA analyses were used for data analysis, and the level of significance was set at p < 0.05. The results showed that differences in the technical performances between these four teams were significant. The Japanese women's football team had a higher ball possession percentage, especially in the final third, during passes, through passes, and during goals in terms of overall competitive ability. In contrast to the playing positions, Chinese defenders had more successful forward passes and crosses. Japanese midfield players showed better performance in terms of passes, pass success, forward passes, cross success, and the forwards performed better during passes and exhibited a higher shot accuracy. The forwards from South Korea had more forward passes and shots and a much higher forward pass accuracy and heading and aerial duel success. Additionally, the key players from China performed more ground duels and had a higher ground duel success. The Japan team performed more passes and had a higher passaccuracy, forward pass success, shots, shot success, and 1vs1 success. South Korea's team had more forward passes and heading duel success. The technical performance of the Chinese Tai Pei team lagged behind other teams. In conclusion, the Japanese women's football team still has a leading position; however, the strength of the Asian women's football team is unbalanced, and from the perspective of technical performance, there is a certain gap between them and those of European and American teams. The recent match performance profiles of these Asian teams can inspire football coaches and managers to determine the latest trends in technical and tactical development and the competitive ability differences of Asian women's football teams and to alter their training sessions to improve players' match performances.